2010
DOI: 10.1111/j.1365-2605.2010.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal heat stress causes a transient alteration in tight junctions and induction of TGF-β expression

Abstract: Specialized junctions, which occur at sites of Sertoli-Sertoli and Sertoli-germ cell contact of seminiferous epithelium, play pivotal roles in spermatogenesis. Slight increase in scrotal temperature can induce oligospermia or azoospermia via increasing germ cell apoptosis. In this study, we demonstrated that the expression of tight junction (TJ) components, such as occludin, claudin-3 and zonula occludens-1 (ZO-1), was reduced 24-48h after a single mild scrotal heat exposure (43°C for 30min), whereas mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 41 publications
8
64
0
2
Order By: Relevance
“…However, the observed heat-induced BTB disruption was partially prevented by administration of a TGF-β antagonist to the testes, concomitant with the heat stress [23]. Furthermore, induction of TGF-β and activation of p38 MAPK after heat treatment were detected in the heat-treated testes, as shown in Figure 7, indicating that TGF-β might be one of the regulators involved in the heat-induced TJ disruption.…”
Section: Heat Stress-induced Sertoli Cell Impairment and Germ Cell Apmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the observed heat-induced BTB disruption was partially prevented by administration of a TGF-β antagonist to the testes, concomitant with the heat stress [23]. Furthermore, induction of TGF-β and activation of p38 MAPK after heat treatment were detected in the heat-treated testes, as shown in Figure 7, indicating that TGF-β might be one of the regulators involved in the heat-induced TJ disruption.…”
Section: Heat Stress-induced Sertoli Cell Impairment and Germ Cell Apmentioning
confidence: 72%
“…We observed a reversible increase in testicular TGF-β3 after heat treatment, which could be involved in the downregulating of TJ-associated proteins and disruption of the BTB [23]. Additionally, p38 mitogen-activated protein kinase (MAPK) signaling pathways were activated in association with the induction of TGF-β3, indicating that the heat-induced increase in TGF-β3 might be involved in regulating BTB dynamics via the p38 MAPK pathway.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Our previous studies demonstrated that temporal heat stress in the testes resulted in a dramatic reduction in the expression of upstream factors, such as androgen receptor (AR), Wilms' tumor gene 1 (WT1), and liver receptor homolog 1 (LHR1) in monkey , Guo et al 2007, Chen et al 2008, rat (Guo et al 2007), and mouse (Cai et al 2011); however, these effects were reversible. The reversible dedifferentiation of Sertoli cells is followed by a temporary reversible disruption of the blood-testis barrier (BTB), which leads to dramatic germ cell apoptosis in the testis .…”
Section: Introductionmentioning
confidence: 99%
“…5,13 Testicular hyperthermia is also reported to disrupt the BTB. 14,15 The molecular mechanisms responsible for the degenerative changes in heat-induced testicular dysfunction remain largely unknown.…”
mentioning
confidence: 99%